2010
DOI: 10.1002/ana.21955
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between atrophy and β‐amyloid deposition in Alzheimer disease

Abstract: There is a strong relationship between beta-amyloid deposition and atrophy very early in the disease process. As the disease progresses to mild cognitive impairment and Alzheimer disease clinical stages, pathological events other than, and probably downstream from, aggregated beta-amyloid deposition might be responsible for the ongoing atrophic process. These findings suggest that antiamyloid therapy should be administered very early in the disease evolution to minimize synaptic and neuronal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
194
3
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 338 publications
(226 citation statements)
references
References 34 publications
25
194
3
3
Order By: Relevance
“…Correlations in earlier (elderly controls or subjective memory complainers) but not later disease stages were found between global amyloid burden measured by carbon-11 Pittsburgh compound B (PiB) PET and global gray matter volume [43] and between medial temporal lobe amyloid load and HV [17]. Significant correlations (r values in the 0.2 range) were found in a pooled sample of HC, MCI, and AD dementia ADNI cases between HV with precuneus and parietal cortices and mean cortical PiB SUVR [44].…”
Section: Discussionmentioning
confidence: 99%
“…Correlations in earlier (elderly controls or subjective memory complainers) but not later disease stages were found between global amyloid burden measured by carbon-11 Pittsburgh compound B (PiB) PET and global gray matter volume [43] and between medial temporal lobe amyloid load and HV [17]. Significant correlations (r values in the 0.2 range) were found in a pooled sample of HC, MCI, and AD dementia ADNI cases between HV with precuneus and parietal cortices and mean cortical PiB SUVR [44].…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of HP volumes appears to be a relatively non-specific event that occurs in response to various degenerative and non- degenerative insults to the brain. Mild degrees of HP atrophy have been associated with neocortical amyloid deposition [37]. Conditions, such as Lewy body disease, depression, stress-related disorders, steroid treatment, seizures, multiple sclerosis, stroke and brain trauma have all been associated with mild HP atrophy [38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies suggested that hypometabolism of glucose in the brain of AD patients is closely linked to cognitive decline [48] and can be indicative of larger subsequent cerebral atrophy [49]. Although cerebral atrophy is not generally related to the regional binding of the Pittsburgh compound B (measuring levels of Aβ aggregation), a relationship between Aβ deposition and atrophy was observed in early AD [49,50]. Interestingly, it was also recently suggested that brain areas of high resting glucose metabolism (reflecting high neuronal activity) in healthy elderly individuals generally correspond to those where the level of regional Pittsburgh compound B uptake is greater in AD patients [51].…”
Section: Brain Metabolism In Admentioning
confidence: 99%